2022
DOI: 10.1093/ee/nvac019
|View full text |Cite
|
Sign up to set email alerts
|

Adventive Larval Parasitoids Reconstruct Their Close Association with Spotted-Wing Drosophila in the Invaded North American Range

Abstract: Two species of larval parasitoids of the globally invasive fruit pest, Drosophila suzukii (Diptera: Drosophilidae), Leptopilina japonica, and Ganaspis brasiliensis (both Hymenoptera: Figitidae), were detected in British Columbia, Canada in 2016 and 2019, respectively. Both are presumed to have been unintentionally introduced from Asia; however, the extent of their establishment across different habitats with diverse host plants used by D. suzukii was unclear. In addition, there was no knowledge of the temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Indeed, it has been found that parasitism of D. suzukii by L. japonica and G. brasiliensis may not occur until 1-3 weeks after the first infestation. 21 This is reflected in our data by the first parasitoids not emerging from incubated fruit until 3 weeks post-infestation (Figs 2 and 3(A)). Additionally, the peak of Leptopilina sp.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Indeed, it has been found that parasitism of D. suzukii by L. japonica and G. brasiliensis may not occur until 1-3 weeks after the first infestation. 21 This is reflected in our data by the first parasitoids not emerging from incubated fruit until 3 weeks post-infestation (Figs 2 and 3(A)). Additionally, the peak of Leptopilina sp.…”
Section: Discussionsupporting
confidence: 68%
“…Like the ACV traps, all Leptopilina samples were labelled as Leptopilina species. We expect that the Leptopilina emerging from fresh berries were more likely to be L. japonica rather than L. heterotoma because L. heterotoma is not often able to overcome the strong immune defence system of D. suzukii 21,27 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations